2021
DOI: 10.2147/cmar.s305464
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Alternative Splicing Signatures in Esophageal Carcinoma

Abstract: Alternative splicing (AS) is a method of increasing the number of proteins that the genome is capable of coding for, by altering the pre-mRNA during its maturation. This process provides the ability of a broad range of proteins to arise from a single gene. AS events are known to occur in up to 94% of human genes. Cumulative data have shown that aberrant AS functionality is a major factor in human diseases. This review focuses on the contribution made by aberrant AS functionality in the development and progress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 156 publications
(229 reference statements)
0
6
0
Order By: Relevance
“…Figure 5 illustrates how alternately spliced isoforms could contribute to both cancer development and progression. Some of these different isoforms can be targeted as potential biomarkers for early cancer detection and diagnosis and as targets for novel therapeutics [ 95 ]. Examples of the targetable splice variants are listed in Table 4 .…”
Section: Alternative Splicingmentioning
confidence: 99%
See 2 more Smart Citations
“…Figure 5 illustrates how alternately spliced isoforms could contribute to both cancer development and progression. Some of these different isoforms can be targeted as potential biomarkers for early cancer detection and diagnosis and as targets for novel therapeutics [ 95 ]. Examples of the targetable splice variants are listed in Table 4 .…”
Section: Alternative Splicingmentioning
confidence: 99%
“…This study identified 2326 AS events in 1738 genes that were differentially spliced in OSCC tissue compared to healthy oesophageal tissue. Of these alternately spliced genes, 1360 genes were predicted to be significantly associated with overall oesophageal cancer patient survival [ 95 ].…”
Section: Alternative Splicingmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, studies have shown that most of the oncogenic splicing events in ESCC seem to be associated with increased expression of subtypes associated with increased proliferation, altered cell junctions, and increased cell migration [ 17 ]. These splicing events are characteristics of the transition from normal oesophageal tissue to oesophageal cancer and subsequent tumour progression and growth, resulting in many of these splicing variants being proposed as viable biomarkers for the diagnosis and prognosis of oesophageal cancer [ 18 ]. Although previous studies have shown that the progression of oesophageal cancer is closely related to AS, there are few studies on the specific mechanism of AS.…”
Section: Introductionmentioning
confidence: 99%
“…Alternative splicing (AS) generates multiple isoforms from a single gene using different combinations of exons. AS is a widespread and complex component of gene regulation in humans and domestic animals, and increasing evidence suggests that aberrant AS functionality can be the cause or consequence of many diseases, and may also associating with economically important traits in domestic animals ( Pan et al, 2008 ; Merkin et al, 2012 ; Gao et al, 2018 ; Dlamini et al, 2021 ). Therefore, splice-altering therapies using animal models have been extensively studied for many diseases such as neurodegeneration and muscular dystrophies, and AS events have also emerged as new biomarkers in some circumstances ( Montes et al, 2019 ; Zhao, 2019 ).…”
Section: Introductionmentioning
confidence: 99%